Work and pay in Japan - Hart, Robert A. 1946-; Kawasaki, Seiichi (Cambridge Univ. Press, 1999)
"This book provides a comprehensive overview of Japanese labour market institutions and practices with respect to employment issues and labour payments
Keywords: Avantages accessoires - Japon; Avantages sociaux - Japon; Labor - Japan; Labor market - Japan; Marché du travail - Japon; Salaires - Gestion - Japon; Salaires - Japon; Salarissen; Secundaire arbeidsvoorwaarden; Travail - Japon; Économie du travail - Europe; Économie du travail - Japon; Économie du travail - États-Unis; Compensation management -- Japan; Employee fringe benefits -- Japan; Labor economics -- Europe; Labor economics -- Japan; Labor economics -- United States; Wages -- Japan; Arbeitsökonomie; Arbeitsmarkt; Lohn; Europa; USA; Japan